Model Pembelajaran POE dengan Media Self Card: Sebuah Studi Eksperimental pada Level Kognitif C5 - Anissa Rahma Sari; Chairul Anwar; Deden Makbuloh; Baharudin Baharudin (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
Islamic Cultural History (ICH) learning should promote students’ higher-order thinking skills, particularly at the C5 cognitive level, which requires argumentative evaluation of historical events. However, at MA Darul Huffaz Lampung, ICH instruction remains predominantly teacher-centered and lacks analytical engagement, resulting in students’ low evaluative abilities. This study aims to analyze the effectiveness of the Predict, Observe, Explain (POE) model integrated with Self Card media in improving students’ learning outcomes in ICH, specifically at the C5 cognitive level.This research employed a quasi-experimental method with a Posttest Only Control Group Design, involving two eleventh-grade classes: an experimental class that implemented the POE model supported by Self Card media, and a control class that received conventional instruction. The research instrument consisted of a learning achievement test designed to measure students’ evaluative (C5) abilities. Data were collected through a posttest and analyzed using normality, homogeneity, and Mann–Whitney tests. The results indicate a significant difference between the two groups, with a significance value of 0.010 (< 0.05), confirming a statistically significant difference in learning outcomes. The POE model supported by Self Card media proved effective in enhancing students’ evaluative abilities through systematic stages of prediction, observation, explanation, and self-reflection.